2019
DOI: 10.1016/j.celrep.2019.11.010
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-27 Is Essential for Type 1 Diabetes Development and Sjögren Syndrome-like Inflammation

Abstract: SUMMARY Human genetic studies implicate interleukin-27 (IL-27) in the pathogenesis of type 1 diabetes (T1D), but the underlying mechanisms remain largely unexplored. To further define the role of IL-27 in T1D, we generated non-obese diabetic (NOD) mice deficient in IL-27 or IL-27Rα. In contrast to wild-type NOD mice, both NOD.Il27−/− and NOD.Il27ra−/− strains are completely resistant to T1D. IL-27 from myeloid cells and IL-27 signaling in T cells are critical for T1D development. IL-27 directly alters the bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…Several studies, including genome-wide association studies ( 63 65 ), demonstrate pathogenic roles of the cytokine IL-27 in T1D. Transgenic NOD IL-27 receptor knockout mice are resistant to disease and blockade of IL-27 delays T1D onset in NOD mice ( 66 , 67 ). MCP-1 is a chemokine involved in immune cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including genome-wide association studies ( 63 65 ), demonstrate pathogenic roles of the cytokine IL-27 in T1D. Transgenic NOD IL-27 receptor knockout mice are resistant to disease and blockade of IL-27 delays T1D onset in NOD mice ( 66 , 67 ). MCP-1 is a chemokine involved in immune cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigation reported that IL-27 not only showed immunomodulatory function, but also was a compensatory effort of dendritic cells against the ongoing inflammation in T1D patients (37). On the contrary, Ciecko et al (38) reported that IL-27 contributes to the pathogenesis of T1D in NOD mice by altering the balance of Treg and T H 1 cells and enhancing the effector function of CD8 T cells, although it was reported that serum IL-27 was strongly elevated in patients with SS (39), which is inconsistent with our results. This may be because SS patients were particularly associated with interstitial lung disease complications in their study.…”
Section: Discussionmentioning
confidence: 97%
“…Analyses were performed in a blinded manner. The wild-type male lacrimal and female salivary gland focus scores represent a subset of our recently published larger wild-type data set 21 that were chosen based on being colony-matched and temporally-matched (i.e., procured within a year of procurement of the knockout samples to which they are compared). Higher magnification representative images were captured with a 10X objective on a Leitz DM-RB research microscope with a Leica DCF700T digital camera using the Leica Application Suite X software (Leica Microsystems, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%